In the afterlight - Bracken, Alexandra (Bracken, Alexandra. Darkest minds., 2014)
When the Children's League disbands, Ruby becomes a leader and forms an unlikely alliance with Liam's brother, Cole, but competing ideals threaten the mission to uncover the cause of IANN and free psi children from the camps.